Problems Of The Concept Of Kafa'ah In Marriage Between Sharifah And Sayyid - Sayyid Abdul Mahdi Al-Farisi; Mohamad Sar’an (Yayasan Cendekia Gagayunan Indonesia, 2024)
The concept of equality in Islamic marriage aims to avoid the negative impact of inequality between husbands and wives in matters of physical, nasab, property, work, fear and religion. However, the aspect of equity in such matters can have a negative impact, namely, caste as a social stratification system that contradicts Islamic teachings as in marriage between Syriph and Sayyid that makes nasab as the main parameter. As for this research, the aim is to find the problematic factors that emerge from the application of the concept of kafa’ah and also to discover the reconceptualization of kafa'ah in the realization of Islamic marriages that do not raise caste systems in society. This research uses descriptive qualitative methods with library study techniques and case studies. And this study concludes that criteria other than religion in the concept of selfishness can cause social stratification even discrimination in society especially in the marriage between Shariah and Sayyid. Therefore, there is a need for a re-understanding of the concepts of self-ishness in society that is more emphasized on the criteria of religion rather than others. Thus, the existence of the existing kafa’ah is very important by placing the kafa’ah proportionally due to the change of times and societies so that the concept of kafa’ah in the fiqih remains relevant and the value of the merit of the establishment of a law kafa'ah can continue to live and in accordance with the mission or basic principles of Islam that is the principle of egalitarianism.